LIQUID PHASE SYNTHESIS OF ETHYL TERT-BUTYL ETHER FROM ETHANOL AND TERT-BUTYL ALCOHOL USING MACROPOROUS AND GELULAR ION EXCHANGE RESIN CATALYSTS - Umar, M.; Saleemi, A. R.; Saha, B. (The Nucleus, 2020)
Ethyl tert-Butyl Ether (ETBE) synthesis using ethanol (EtOH) and tert-butyl alcohol (TBA) was studied under atmospheric pressure conditions with different macroporous and gelular ion exchange resin catalysts. The catalysts used were PuroliteÂ® (CT-124, CT-145H, CT-151, CT-175, CT-275) and Amberlyst-15 and 35, all in H+ form. All catalysts were employed for ETBE synthesis under identical conditions and suitable catalyst was decided on the basis of conversion and selectivity. Among the catalysts studied, CT-124 produced the best results and was used for further studies. Effect of temperature, feed molar ratio of reactants and catalyst loading was studied and the optimum conditions found were: 343 K temperature, 1:2 feed mole ratios and 5 % catalyst loading. Kinetic modeling was performed using various heterogeneous reactions models and it was found that Quasi-Homogeneous model represented the system more adequately.